2012
DOI: 10.9799/ksfan.2012.25.4.807
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Activity of Smilax china L. Leaf Teas Fermented by Different Strains

Abstract: To evaluate the functional characteristic and availability for drinking of the fermented Smilax china leaf tea by using different microbial species, various fermented leaf tea was prepared by non-fermentation (C), or the fermentation of Saccharomyces cerevisiae (S), Bacillus sp. (B), Bifidobacterium bifidus (L), Monascus pilosus (M) and Aspergilus oryzae (A), and sensory and antioxidant parameter of each brewed tea was observed. The color of the A tea was red, but the other teas were yellow in color. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…The highest amount of total content of identified phenolic acid and flavonoids was found in SCL processed by steaming. Similar to our finding, the highest amount of total polyphenols was found in steamed SCL, while the lowest was detected in that fermented by Aspergillus oryzae . It was reported that Aspergillus oryzae oxidized polyphenols in SCL, then formed a reddish color of polyphenol oxide, relating to the reddish phenomenon .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The highest amount of total content of identified phenolic acid and flavonoids was found in SCL processed by steaming. Similar to our finding, the highest amount of total polyphenols was found in steamed SCL, while the lowest was detected in that fermented by Aspergillus oryzae . It was reported that Aspergillus oryzae oxidized polyphenols in SCL, then formed a reddish color of polyphenol oxide, relating to the reddish phenomenon .…”
Section: Resultssupporting
confidence: 90%
“…Similar to our finding, the highest amount of total polyphenols was found in steamed SCL, while the lowest was detected in that fermented by Aspergillus oryzae. 28 It was reported that Aspergillus oryzae oxidized polyphenols in SCL, then formed a reddish color of polyphenol oxide, relating to the reddish phenomenon. 28 It was assumed that ethanol-soluble polyphenols produce color components owing to fermentation by Aspergillus oryzae.…”
Section: Identification Of Phenolic Acid and Flavonoids In Scl By Lc-mentioning
confidence: 99%
“…Furthermore, antioxidant capacity was shown to be the greatest in SC leaf fermented by Aspergillus oryzae among microbial fermentation strains (Kim et al, ). Lee et al () also showed that overall sensory acceptance in SC fermented by Aspergillus oryzae was higher than any other microbial strains. When it comes to enhancing antioxidant capacity in SC by fermentation, hepatic lipogenesis affected by diverse antioxidant enzymes could be altered.…”
Section: Introductionmentioning
confidence: 95%
“…Owing to its antioxidant and antimicrobial capacities, SC has been also used for food packaging for rice cakes to supply good flavor as well as inhibit microbial growth (Shim, ). SC has drawn an attention for providing bioactive components which are responsible for protecting against age‐related diseases induced by a generation of reactive oxygen species (ROS) (Lee, Lee, Kim, Kang, & Suh, ; Shim, ). For instance, Shim () identified volatile components including 3‐hydroxy benzoic acids and 1,2‐benzenediol in SC extract, suggesting that it can be substituted with synthetic antioxidants in the food system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation